A scale-dependent bias on linear scales: the case for H i intensity mapping at z = 1. Issue 4 (10th October 2017) - Pénin, Aurélie; Umeh, Obinna; Santos, Mario G.
Abstract: Neutral hydrogen (H i ) will soon be the dark matter tracer observed over the largest volumes of Universe, thanks to the 21-cm intensity mapping technique. To unveil cosmological information, it is indispensable to understand the H i distribution with respect to dark matter. Using a full one-loop derivation of the power spectrum of H i, we show that higher order corrections change the amplitude and shape of the power spectrum on typical cosmological (linear) scales. These effects go beyond the expected dark matter non-linear corrections and include non-linearities in the way the H i signal traces dark matter. We show that, on linear scales at z  = 1, the H i bias drops by up to 15  per cent in both real and redshift space, which results in underpredicting the mass of the haloes in which H i lies. Non-linear corrections give rise to a significant scale dependence when redshift space distortions arise, in particular on the scale range of the baryonic acoustic oscillations (BAOs). There is a factor of 5 difference between the linear and full H i power spectra over the whole BAO scale range, which modifies the ratios between the peaks. This effect will also be seen in other types of survey and it will be essential to take it into account in future experiments in order to match the expectations of precision cosmology.